Imitação e Exílio na Poesia Didática de Rafael Landívar e de José Rodrigues de Melo - Silva, Roberto Gonoring D'Assumpção (2024)
Among the numerous examples of didactic poetry writing inside the Society of Jesus in the 17th and 18th centuries, we take two works from this context that, having been written in Italy, sing the American countryside in their verses, the De Rusticis Brasiliae Rebus (1799), by José Rodrigues de Melo, and the Rusticatio Mexicana (1781), by Rafael Landívar, as objects of study in order to offer a reading focusing on some of their constituent aspects. Both Melo and Landívar, besides having studied the order’s curriculum, based on the Ratio Studiorum, were exiled from the Americas during the Suppression of the Society of Jesus by the lands belonging to the Portuguese and Spanish monarchies, respectively. Considering such similarities, we seek, on one hand, to analyze the works according to literary precepts and expectations based on rhetoric, in order to promote a non-anachronic reading of a literary genre that has become moribund since the 19th century, and, on the other, to constantly contrast the poetic choices made by each author, noting their similarities and differences. In this process, therefore, we take the Jesuit reading of classical rhetoric, based on Cicero and Quintilian and operating through the imitation of models and tópoi, as the practical literary theory whose role it played in the Early Modern Age. With this basic theoretical apparatus, our work deals firstly with how Melo and Landívar’s education as Jesuit priests, with all the theory made available to them by the Ratio Studiorum’s curriculum, influenced the poems’ themes and stylistic choices in regards to the tradition of didactic poetry; secondly, how and to what persuasive ends the poets represented the biographical fact of their exile from America; and finally, how Melo and Landívar differ from one another as to the language and structure of their didactic poems, as well as what effects these difference cause on the poet’s image. What we observe in the poems is a constant transformation both of the structure and of the matter common to didactic poetry from Antiquity and contemporary to the authors, especially in regards to the presence of an addressee, the instructional tone through imperative verbs and technical preceptive as opposed to a narrative or descriptive language, the characterization of the farmer that works intensely in the represented landscape and the presentation of the poem’s singing voice’s éthos. As we discuss, even though each poet utilizes different mechanisms to deal with the aforementioned aspects, both coincide in arguing, subtly, against the jesuits’ expulsion from the Americas, seeking to demonstrate the benefits brought by the order’s members to the continent.